The advertisement call of the Colombian endemic glassfrog Rulyrana susatamai (Anura: Centrolenidae) - Galindo, Carlos Alberto; Viuche-Lozano, Andres; Bernal, Manuel Hernando (Zootaxa, 2020)
Anuran calls are conspicuous, diverse and subject to sexual selection. Many types of calls are described, but the most commonly studied is the advertisement call (Wells 2007; Toledo et al. 2014). Advertisement calls in anurans are emitted by males and some females (Toledo et al. 2014), and have the function of attracting conspecific mates and repelling male competitors. Because the advertisement calls of many species differ by such a magnitude that they serve as premating species (Heyer et al. 1996), it has been demonstrated that advertisement calls play an important role in species recognition, reproductive isolation, and may reflect evolutionary relations among taxa (Wells 2007; Escalona et al. 2018).